Dropout dilemma: Towards a better understanding of youth sport disengagement - Wright, E. M.; Liardi, V. O. J.; McCullagh, P. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Sport plays a critical role in the development of both physical competencies and social skills (Bailey, 2006). Dropout statistics for organized youth sport continue to present as a hazard for sport leaders and physical educators (Joesaar, Hein, & Hagger, 2011). Thus it is critical to examine the underlying factors that may act as a catalyst towards youth sport disengagement. Methods: After conducting a thorough review of literature on reasons youth dropout from sport, a list of 8 factors (didn`t like coach, wasn`t fun, needed time for school, wasn`t good enough, wanted time for non-sport activities, too much focus on winning, injured, other sports took up too much time) that may uniquely contribute to a decision to dropout of one`s sport was generated (Butcher, Linder & Jones, 2002; Seefeldt & Ewing, 1989). Two hundred and sixty nine 9th graders in various high schools throughout Michigan, USA, completed questionnaires. Previous sport participation in each of grades 6 through 8 was assessed, as well as current sport participation through their first year of high school. Results: A multiple regression analysis attempted to predict overall sport engagement through grades 6-8 from the list of dropout reasons. Results indicated that the `other sports took up too much time` reason significantly contributed to the model. Secondly, a binary logistic regression was conducted in order to gauge if any of the 8 reasons could distinguish those who continued sport participation into high school versus those who dropped out. It was revealed that the reasons `too much focus on winning` and `other sports took up too much time` significantly contributed to the model. Discussion: An overemphasis on winning was the only factor that contributed to a discontinuation of all sport. Earlier research shows that a mastery climate is associated with enduring participation, whereas a competitive climate is associated with dropout (Sarrazin et al., 2002). Self-determination theory (Deci & Ryan, 1985) is a suitable framework from which to study sport persistence, as evidence indicates that underscoring external regulators (i.e., wins) has adverse effects on sport adherence. Teens may be susceptible to developing an antipathy towards sport if extrinsic motivators are encouraged.